1999
DOI: 10.3354/meps184055
|View full text |Cite
|
Sign up to set email alerts
|

Using cell cycle analysis to estimate in situ growth rate of the dinoflagellate Dinophysis acuminata:drawbacks of the DNA quantification method

Abstract: previously estimated the duration of the terminal event (the duration of the S + G2 + M phases) in this species to be 11 to 13 h. A 12 h duration of the terminal event in this study would yield specific growth rates of 0.69 to 0.75 d" We conclude that the number of cells that can be measured using epifluorescence microscopy (a few hundred per sample) is too low to allow detection of a low degree of synchronisation, especially with regard to the S phase. Estimations of in situ growth rate of poorly synchronised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…The observed maximum growth rate is comparable to previous in situ estimates of D. acuminata from the Baltic Sea: 0.49 ± 0.05 to 0.59 ± 0.13 d -1 (Granéli et al 1997) and 0.69 to 0.75 d -1 (Gisselson et al 1999), measured at 10 and 13°C, respectively. Recently, Kim et al (2008) found somewhat higher maximum growth rates (0.80 d .…”
Section: Growth and Grazingsupporting
confidence: 76%
“…The observed maximum growth rate is comparable to previous in situ estimates of D. acuminata from the Baltic Sea: 0.49 ± 0.05 to 0.59 ± 0.13 d -1 (Granéli et al 1997) and 0.69 to 0.75 d -1 (Gisselson et al 1999), measured at 10 and 13°C, respectively. Recently, Kim et al (2008) found somewhat higher maximum growth rates (0.80 d .…”
Section: Growth and Grazingsupporting
confidence: 76%
“…There- ), was a discrete, rapid (2 h) process. In contrast, Gisselson et al (1999), who applied the same technique to populations of D. acuminata from the Gullmar Fjord (Skagerrak, Sweden), found a constantly high percentage (23 to 43%) of cells with a double content of DNA (G2 + M cells), very poor synchronisation, and lack of a clear cell-division pattern. These latter authors concluded that the microfluorimetric method applied to several hundreds of cells was inadequate to detect low degrees of synchronization, especially with regard to the S phase.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might explain the observations of Gisselson et al (1999): they applied the method of Carpenter & Chang (1988) to natural populations of Dinophysis acuminata after a sudden decrease in insolation, and found a constantly high percentage (23 to 43%) of cells with a 2q content of DNA and no synchronization. Our interpretation of the results of Gisselson et al (1999) is that they were dealing with a population stressed by changes in weather conditions, and by the late time of year in the dynamic waters of the Gullmarfjord that had a very low division rate and probably an accumulation of 2qDNA cells. Another case of poor synchronization was described by Carpenter et al (1995) in a D. norvegica population in the Baltic Sea thermocline under low light intensity.…”
Section: Cell Division Patterns In Natural Populations Ofmentioning
confidence: 95%
“…Using these microfluorometry techniques, t d can be estimated in populations where cell division is to some degree synchronized. This is accomplished by monitoring changes in the relative proportion of G 1 to S + G 2 + M phase cells through time and applying deconvolution techniques to establish the length of the terminal event (Whitely et al 1993, Gisselson 1999. In this study, the method employed was less sensitive and only capable of detecting M phase cells.…”
Section: Methodsmentioning
confidence: 99%